Study on the reduction of aeroacoustic noise from a circular cylinder attached with cylindrical rings - Hidetoshi SANO; Shunsuke YAMADA; Yuki FUNAMI; Hajime NAKAMURA (Nihon Kikai Gakkai ronbunshu, 2020)
The reduction of aerodynamic noise emitted from a circular cylinder was investigated experimentally by attaching the cylindrical rings arranged in the axial direction of the cylinder. The Reynolds number based on the cylinder diameter d was ranged from Re = (2.0 to 3.9) × 104. The sound pressure level was reduced up to 14 dB by attaching the rings of the diameter Dr/d = 1.3 and the width W/d = 1.0, which was arranged at the spanwise pitch P/d = 4. At this configuration, a 1/3 octave band analysis showed a reduction of the sound pressure up to 26 dB at the frequency band of the vortex shedding from a circular cylinder. The result of the PIV measurements showed that the reduction of the sound pressure is related to the reduction of the Reynolds stress in the wake, which is mainly caused by the suppression of the periodic vortex shedding.